1997
DOI: 10.1007/s001120050114
|View full text |Cite
|
Sign up to set email alerts
|

Durchführung eines neuen Therapiekonzepts für Nephroblastome im Bereich der Gesellschaft für Pädiatrische Onkologie und Hämatologie SIOP 9/GPOH

Abstract: Mit Unterstü tzung der Deutschen Krebshilfe (M 61/89/Lu 1) Priv.-Doz. Dr. R. Ludwig, Sektion Hä matologie/Onkologie, Universitä ts-Kinderklinik, Im Neuenheimer Feld 150, D-69120 Heidelberg 132 KLINIK UND FORSCHUNG Abb. 1. Wahrscheinlichkeit fü r das ereignisfreie Ü berleben aller Nephroblastome (n = 486) der SIOP 9/GPOH-Studie aufgeschlü sselt nach Protokoll-und Studienpatienten. Als Ereignisse (n = 85) wurden Rezidive, Bilateralisationen und therapiebedingter Tod gewertet, KI Konfidenzintervall, Datenstand 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The higher toxicity rates in our patients, with 10% of all patients fulfilling the NWTS criteria for severe hepatotoxicity compared to the nonirradiated NWTS patients with standard chemotherapy and the UKW patients, may result from the fact that we used a sample representing 95% of all nephroblastomas registered by the German Childhood Cancer Registry [12]. Also, the GPOH centers joined the SIOP-9 trial 11 months after it had started, and by that time some SIOP centers had already reported their experience with increased hepatotoxicity [7].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The higher toxicity rates in our patients, with 10% of all patients fulfilling the NWTS criteria for severe hepatotoxicity compared to the nonirradiated NWTS patients with standard chemotherapy and the UKW patients, may result from the fact that we used a sample representing 95% of all nephroblastomas registered by the German Childhood Cancer Registry [12]. Also, the GPOH centers joined the SIOP-9 trial 11 months after it had started, and by that time some SIOP centers had already reported their experience with increased hepatotoxicity [7].…”
Section: Discussionmentioning
confidence: 96%
“…A higher percentage of patients with VOD in the report on SIOP-9 trial patients (8%) in comparison to 4.8% in our analysis may also be due to sample differ-ences. Because we included all patients with unfavorable histology and stage IV, as well as nonresponders to preoperative treatment, we had a higher rate of patients treated with AMD at double dose on 1 day [12,19]. This group developed no hepatotoxicity (Table V).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We analyzed the status of the entire WT1 gene in 64 cases of WTs predominantly from patients with preoperative chemother-apy and ascertained through the German SIOP9͞GPO study (46). First we studied 32 consecutive cases, followed by patients selected for GU anomalies and bilateral tumors.…”
mentioning
confidence: 99%